Pengelolaan Terminal 3 Bandara Internasional Soekarno-Hatta Menuju Aspek ECO-MODERN Airport - Agustini, Endang Dwi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Airport could potentially contribute to environmental contamination, such as air pollution resulting from C02 emissions as a result of the operation of aircraft and vehicles at airports, waste water generated can pollute the environment and waste both from the passengers as well as from restaurants and offices. Of the impact can be drawn formulation of the problem is haw pollution, sewage and waste are managed in an effort to minimize and slow down environmental damage. The method in this study is to use quantitative methods dikualitatijkan by calculating the rating scale of primary data collection by giving questionnaires to the respondents in this case is the passenger's departure at the terminal 3 as well as structured interviews with the management of PT Angkasa Pura II (Persero). Analysis of the discussion is done by check-list with the results of environmental monitoring component elements of the fulfillment of the required parameters and the results of respondents' answers are calculated by weighting the numbers with the resulting value is 92.04% interval value is in the category of shows